Perhitungan Nilai Nisbah Hantaran Sedimen dengan Menggunakan kurva Sedimen dan Model Erosi Tanah - Nining Wahyuningrum; Putu Sudira; Haryono Supriyo; Sambas Sabarnurdin (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2014)
Prolonged soil erosion and sedimentation have negative effect on land quality showing by decreasing land productivity, in addition, sedimentation process may cause decreasing function of hydrologic infrastructures. In watershed scale it is important to monitor both important processes. The relationship between the amount of onsite erosion and sedimentation at the watershed outlet is formulated in the Sediment Delivery Ratio (SDR). SDR is the ratio between the erosion that occurs in the entire basin with the amount of sediment in the outlet of a watershed. This study aimed to calculate SDR value of two watersheds which have different topographic condition and land cover types composition. The study was conducted in two sub-watersheds namely Tapan and Ngunut I. Erosion calculation used USLE formulae while prediction of water discharge and sediment discharge utilized rating curve and sediment rating curve. The study shows that (1) SDR of Tapan is higher than SDR of Ngunut I, it indicates that there are others source of sediment beside sheet erosion which is transported to the outlet of watershed, (2) The value of SDR fluctuate according to fluctuations in monthly rainfall and runoff, (3) SDR is less sensitive to land cover types rather than of topographic factor (slope, drainage density an watershed area).ABSTRAKProses erosi dan sedimentasi yang berkepanjangan dapat memberi pengaruh negatif terhadap kualitas lahan, selain itu proses sedimentasi juga dapat mengakibatkan menurunnya fungsi bangunan hindrologis. Dalam skala Daerah Aliran Sungai (DAS) kedua proses ini penting untuk dimonitor. Hubungan antara besarnya erosi ditempat dan sedimentasi pada luaran DAS dirumuskan dalam bentuk nisbah hantaran sedimen (Sediment Delivery Ratio, SDR). SDR merupakan rasio antara erosi yang terjadi pada seluruh DAS dengan jumlah sedimen pada daerah outlet. Studi ini bertujuan menghitung besarnya nilai SDR pada dua DAS dengan kondisi topografi dan jenis penutupan lahan yang berbeda. Penelitian dilakukan di dua sub DAS Ngunut I dan Tapan. Perhitungan erosi dilakukan dengan metode USLE sedangkan perhitungan sedimen dengan menggunakan rating curve dan sediment rating curve. Hasil analisis menunjukkan bahwa (1) Diperoleh nilai SDR Sub DAS Tapan lebih tinggi (2,37) daripada nilai SDR Sub DAS Ngunut I (0,047). Hal ini mengindikasikan adanya sumber materi sedimen lain selain dari erosi lembar yang terbawa ke luaran DAS, (2) Nilai SDR berfluktuasi sesuai dengan fluktuasi bulanan hujan dan limpasan, (3) Jenis penutupan lahan kurang berpengaruh terhadap SDR dibandingkan dengan topografi (kemiringan lahan, kerapatan aliran dan luas DAS).